Software performance modelling using PEPA nets. - Gilmore, Stephen (Software engineering notes.)
Modelling and analysing distributed and mobile software systems is a challenging task. PEPA nets---coloured stochastic Petri nets---are a recently introduced modelling formalism which clearly capture important features such as location, synchronisation and message passing. In this paper we describe PEPA nets and the newly-developed platform support for software performance modelling using them. Crucial to this support is the compilation from PEPA nets into Hillston's PEPA stochastic process algebra in order to access the software tools which support the PEPA algebra. In addition to derivation of steady state performance measures, this suite of tools allows properties of the system to be verified using model-checking. We show the application of PEPA nets in the modelling and analysis of a secure Web service.